The combination of miacalcic, calcium lactate, and vitamin C as postextracted alveolar bone resorption inhibitor - Sri Kentjananingsih (Universitas Airlangga, 2010)
Background: Tooth extraction can cause alveolar resorption, and will reduce the denture retention. The process of bone resorption looks like the process of osteoporosis. Calcium and vitamin D supplementation is the rational therapy for minimizing bone loss. Miacalcic is the drug of choice for osteporotic patient. Purpose: This study is aimed to know whether the combination of miacalcic, calcium lactate, and vitamin C are effective in inhibiting post extracted alveolar resorption. Methods: Thirty three healthy postmenopausal women were chosen as samples and they were classified randomly into control group (without treatment), 1st experiment group (treatment was started 3 months post extraction), and 2nd experiment group (treatment was started at the 2nd day post extraction). The treatment was done by giving miacalcic nasal spray, calcium lactate 500 mg and vitamin C 100 mg tablets every morning in 10 days every month for 3 months. X-ray photo of the post extracted area were taken an hour, 3 months, and 6 months post-extraction. Results: After 6 month, there was significant difference in buccolingual thickness decreasing among three groups (p<0.05). The maximum mean difference of buccolingual thickness decreasing was 0.72 mm, between control and 2nd experiment groups. There was no significant difference about decreasing bone density among them (p>0.10). The maximum difference of the mean of density decreasing was 1,906 g/cm2/mm between control and 2nd experiment groups. The increasing density mostly occurred in the 2nd experiment group. Conclusion: The combination of miacalcic, calcium lactate, and vitamin C are effective for inhibiting alveolar resorption, although statistically there was no significant difference about bone density decreasing.